The Emergency Severity Index (ESI) Usage: Triage Accuracy and Causes of Mistriage - Sari, Silvia Ramdini; Fajarini, Melati (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
Errors in determining triage criteria can endanger patient safety so the cause must be addressed. But it is not yet known the accuracy of triage and the cause of mistriage. This study aims to identify the accuracy of the level of gravity of the Emergency Severity Index (ESI) triage system and evaluate the causes of mistriage in the Emergency Department (ED). Descriptive research with the retrospective review was conducted for 20 days which were randomly selected between January 1st and December 31st, 2021 at a hospital in Jakarta. A total of 199 randomly selected ESI triage documentation from medical records and a self-developed triage precision observation sheet consisting of 17 items were given to three experts to examine the accuracy of the triage and the cause of the mistriage. The frequency distribution found the triage accuracy reach 124 (62,3%) triage documents, and the leading cause of mistriage is an error in applying the main complaint 32 (42,7%). ED nurses should improve their skills in determining triage levels. Hospital institutions should make efforts to improve the triage skills of ED nurses and for further research on methods to increase the accuracy of the triage. Abstrak: Kesalahan dalam menentukan kriteria triase dapat membahayakan keselamatan pasien sehingga penyebabnya harus segera diatasi. Namun belum diketahui ketepatan triase dan penyebab terjadinya mistriage. Penelitian ini bertujuan untuk mengidentifikasi akurasi triase menggunakan Emergency Severity Index (ESI) dan mengevaluasi penyebab mistriase di Instalasi Gawat Darurat (IGD). Penelitian deskriptif dengan tinjauan retrospektif dilakukan selama 20 hari yang dipilih secara acak antara 1 Januari hingga 31 Desember 2021 di sebuah rumah sakit di Jakarta. Sebanyak 199 dokumentasi triase ESI dari rekam medis dan lembar observasi presisi triase yang dikembangkan sendiri yang terdiri dari 17 item diberikan kepada tiga ahli untuk memeriksa keakuratan triase dan penyebab mistriase. Distribusi frekuensi ditemukan akurasi triase mencapai 124 (62,3%) dokumen triase, dan penyebab utama mistriage adalah kesalahan dalam menerapkan keluhan utama 32 (42,7%). Perawat UGD harus meningkatkan keterampilan mereka dalam menentukan tingkat triase. Institusi rumah sakit harus melakukan upaya untuk meningkatkan keterampilan triase perawat UGD dan untuk penelitian lebih lanjut tentang metode untuk meningkatkan akurasi triase.